Patient Albright in the hunt - Malay, Mail (Malay Mail, 2017)
KOTA KINABALU — A calm approach paid off for local hope Albright Chong Ming Soon as he trails by two strokes after yesterday's opening round of the 115th Malaysian Amateur Open.